Case Report: Immune checkpoint inhibitor–induced multiorgan vasculitis successfully treated with rituximab - Qureshi, Sehrish; Arani, Naszrin; Parvathareddy, Vishnu; Tchakarov, Amanda; Abdelrahim, Maen; Suarez-Almazor, Maria; Zhang, Jianjun; Gibbons, Don Lynn; Heymach, John; Altan, Mehmet; Abudayyeh, Ala (Frontiers in Nephrology, 2023)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of cancer. ICIs have a unique side effect profile, generally caused by inflammatory tissue damage, with clinical features similar to autoimmune conditions. Acute kidney injury from ICIs has been well studied; incidence ranges from 1% to 5%, with higher incidence when combination ICI therapies are used. Although the overall reported incidence of ICI-associated glomerulonephritis is less than 1%, vasculitis is the most commonly reported ICI-related glomerulonephritis. Other biopsy findings include thrombotic microangiopathy, focal segmental glomerulosclerosis, minimal change disease, and IgA nephropathy with secondary amyloidosis. We report a case in which a woman previously treated with the PD-L1 inhibitor durvalumab for locally advanced non-small cell lung cancer with pre-existing clinically asymptomatic antineutrophil cytoplasmic (anti-PR3) antibody presence, who later developed multi-organ vasculitis after ICI exposure, which was successfully treated with rituximab, with continued cancer remission for 3 years.